Farm diversification strategies, dietary diversity and farm size: Results from a cross-country sample in South and Southeast Asia - Tacconi, Francesco; Waha, Katharina; Ojeda, Jonathan Jesus; Leith, Peat; Mohammed, Caroline; Venables, William N.; Rana, Jai C.; Bhardwaj, Rakesh; Yadav, Rashmi; Ahlawat, Sudhir Pal; Hammond, James; Wijk, Mark T. van (Elsevier, 2023)
South and Southeast Asia host almost half of the world's undernourished people. Food and agricultural systems in these regions are highly dependent on the production and consumption of staple cereals such as rice, maize and wheat. More diverse farming systems can potentially improve rural people's nutrition, while reducing the environmental impact of agriculture. Yet, it remains uncertain whether farm diversification is always the most suitable and viable strategy for all types of smallholder farms. We use generalised linear regression models to analyse the farm diversification strategies of 4772 rural households in Cambodia, India, Lao PDR and Vietnam. Our analysis is twofold and focuses first on drivers of farm diversification, and second, on the impacts of farm diversification and other livelihood strategies on dietary diversity. We find that (1) farm diversification is significantly influenced by environmental and climate variables, including rainfall patterns, as well as household and farm characteristics such as farm size and education level; and (2) farm diversification, market orientation and off-farm income generation are all strategies that can improve household and individual dietary diversity. However, their relative effects resulted influenced by farm size. Specifically, the positive effect of farm diversification on dietary diversity was larger for smaller farms, while it decreased for farms of larger size that may improve their diet more by increasing their engagement in off-farm activities and markets. These findings highlight that characteristics such as farm size can represent substantial determinants in production and consumption decisions, suggesting the importance of understanding and considering the type of farm and the situational context of analysis when targeting interventions for improving smallholder farm livelihoods.